Spirituality During the COVID-19 Pandemic: An Online Creative Arts Intervention With Photocollages for Older Adults in Italy and Israel - Keisari, Shoshi; Piol, Silvia; Orkibi, Hod; Elkarif, Talia; Mola, Giada; Testoni, Ines (Frontiers in Psychology, 2022)
The present study aimed to examine how expressions of spirituality were stimulated and reflected in an online creative arts intervention for older adults during COVID-19 lockdowns. The online process focused on the creation of digital photocollages together with narrative elements of dignity therapy. Twenty-four Israeli and Italian community-dwelling older adults aged 78–92 participated in a three-session online intervention involving the production of three photocollages. The visual and verbal data (participants’ chosen photos and photocollages, and transcripts of the sessions) were qualitatively analyzed within an abductive framework. Four themes were generated, representing the four domains of spirituality that were stimulated by and expressed in the process: (1) Connectedness with the self, (2) connectedness with others, (3) connectedness with the environment, and (4) connectedness with the transcendent. The findings show how photographs can serve as projective visual stimuli which elicit personal content through spontaneous thinking, and they reveal the multifaceted nature of spirituality, wherein each domain nourishes the others. Overall, the findings illustrate how creative arts intervention guided by the tenets of dignity therapy can contribute to the spiritual care of older adults during periods of social isolation, or to the spiritual support provided in palliative care.